1979
DOI: 10.1002/ar.1091950310
|View full text |Cite
|
Sign up to set email alerts
|

A Morphometric analysis of the glomerular capillary wall of a new strain of genetically hypertensive mice

Abstract: An investigation was performed on a new strain of genetically hypertensive mice to study those aspects of the renal glomerulus which have in the past been implicated in the etiology of renal parenchymal hypertension. Morphometric analyses were carried out utilizing a computerized graphic data analysing system on information obtained through transmission electron microscopy. Chronically hypertensive animals exhibited thinner basement membranes with numerous sub-epithelial focal thickenings, which were largely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Original characterization studies of hypertensive Schlager mice found that older hypertensive animals (43–50 weeks old) had a significantly smaller basement membrane mean width with numerous sub-epithelial focal thickenings compared to normotensive mice. There was no difference in epithelial slit pore width, however, (Rosenberg et al, 1979). This suggests that even with a longer hypertensive duration nephropathy is not severe in this model.…”
Section: Discussionmentioning
confidence: 91%
“…Original characterization studies of hypertensive Schlager mice found that older hypertensive animals (43–50 weeks old) had a significantly smaller basement membrane mean width with numerous sub-epithelial focal thickenings compared to normotensive mice. There was no difference in epithelial slit pore width, however, (Rosenberg et al, 1979). This suggests that even with a longer hypertensive duration nephropathy is not severe in this model.…”
Section: Discussionmentioning
confidence: 91%
“…Hypertensive BPH/2 mice have similar kidney-to-body weight ratio as BPN/3 (Schlager et al, 1979) but have fewer nephrons per kidney (Rosenberg et al, 1982). Morphometric analysis of kidneys from older BPH/2 mice showed none of the characteristic features of renal parenchymal pathology (Rosenberg et al, 1979) indicating that major morphological differences in the kidney are not likely driving the hypertension. However, the available filtration surface area in juxtamedullary glomeruli in BPH/2 mice is less than half that of BPN/3 mice while the superficial cortical glomeruli were comparable between strains (Rosenberg et al, 1982).…”
Section: Heart Vessel and Kidney Structure And Functionmentioning
confidence: 97%
“…An important phenotypic difference observed in BPH/2 mice is that their body weight is lower compared with BPN/3 mice (Rosenberg et al, 1982; Buu et al, 1987). However, hypotensive BPL/1 mice also have lower body weight than BPN/3 mice suggesting that this attribute is not likely to be associated with the hypertension (Rosenberg et al, 1979). Early studies suggested that water intake of female BPH/2 mice was 20% greater than the normotensive strain but if offered a choice, they preferred solutions of lower NaCl or KCl concentration (Bachmanov et al, 1998).…”
Section: Metabolic Abnormalities In Bph/2 Micementioning
confidence: 99%
“…In a previous study [18] no evidence of glomerular sclerosis such as that described by Cluirg and Grishman [7] were observed. There appeared to be no mesangial changes other than that of a decreased cell number [19] as might be expected in glomerular pathologies [6,17] nor was there evidence of amyloid [14].…”
Section: Discussionmentioning
confidence: 75%
“…As the Schlager strain of genetically hypertensive mice [21] demonstrated the presence of certain structural changes in the glomerular capillary wall of the hypertensive animals [18] along with changes in glomerular cellularity [19]. The present investigation was undertaken in order to further study in a quantitative manner various structural aspects of the kidney of the hypertensive mouse.…”
Section: Introductionmentioning
confidence: 99%